Worker associations in the construction of model popular housing (Santiago, Chile, 1925-1930) - Morales Barrientos, Diego (Cuadernos de Historia, 2023)
In the city of Santiago, there was a chronic lack of hygienic housing for the popular classes throughout the first decades of the 20th century. To mitigate this, in 1925 a novel credit policy was implemented for workers with higher stable incomes. At least two popular housing sites came to be due to this policy: The Society of Craftsmen “La Unión” and the Cooperative of Typographers. It is explained why these entities were successful as well as their activities, highlighting the tight link they had with the reformist elite of the time.